Green Green HRM Research Gaps and Future Agenda: A Systematic and Bibliometric Synthesis - Ahmad, Mauledy; Lova, Anggil Nopra; Santoni, Alvia; Desiyanti, Rika (The Future of Education Journal, 2025)
In response to the increasing demand for environmentally sustainable organizational practices, Green Human Resource Management (GHRM) has gained prominence as a strategic integration of ecological values into core HRM functions. Despite growing scholarly interest, GHRM research remains fragmented and methodologically limited, often lacking contextual and longitudinal insights. This study aims to systematically synthesize existing literature and identify key research gaps and future directions. Using a Systematic Literature Review (SLR) combined with bibliometric analysis, 31 peer-reviewed articles indexed in Scopus from 2021 to 2025 were critically examined. VOSviewer software was employed to visualize co-occurring keywords, author networks, and thematic clusters. The findings indicate that core GHRM practices such as green recruitment, training, and appraisal are central to fostering innovation, sustainability performance, and organizational transformation. Recent trends highlight a shift towards integrating digitalization, artificial intelligence, and Industry 4.0 into GHRM frameworks. However, research remains largely concentrated in specific regions and sectors, with limited representation of SMEs, non-profit institutions, or diverse cultural contexts. Additionally, external stakeholder engagement, ESG-linked HR strategies, and data-driven sustainability reporting are underexplored. This study proposes an integrative GHRM model linking global sustainability pressures with strategic HR outcomes including green innovation, digital alignment, and stakeholder accountability. The article contributes both conceptually and practically by consolidating the theoretical base of GHRM and informing future research agendas that are inclusive, adaptive, and forward-looking.